EXPRESSION OF BUD FERTILITY OF GRAPEVINE IN FUNCTION OF DIFFERENT PRUNING TIMES AND DOSES OF NITROGEN - Carvalho, Ruy Inacio Neiva de; Simões, Fabiano (Scientia Agraria, 2006)
The culture treatment applied in the grapevine interferes in vegetative and reproductive growth of new grapevine branches. The period of pruning and doses of nitrogen fertilizer before of natural sprout can modify the vegetative growth and the expression of fertility of grapevine’s buds. The objective of this work was to evaluate this expression in function of different periods of pruning and doses of nitrogen. The technical of pruning utilized in ‘Niagara Rosada’ grapevines was the short hibernal pruning, where two buds were left in the branches (basal and apical), realized in three differents period (early, intermediate and later), associated with nitrogen fertilizer with 0, 50 and 100 g of N per plant. The number of bunch per bud, percentage of damaged buds, percentage of dormant buds, percentage of inhibition of buds fertility and vigor of new branches were evaluated. The real fertility was evaluated in laboratory and compared with the fertility express in field. The best expression of buds fertility occurred with the intermediated pruning without fertilizer and early pruning with 50 g N per plant for the production of bunch in branches originated from the basal bud of the prunned branch. The later pruning with 100 g of N per plant stimulated the production of bunch in branches originated from the apical bud of the prunned branch.